Legal Review of the Execution of Movable Objects Based on Fiduciary Guarantees Against Default Debtors from the Perspective of Islamic Law - Rahman, Arief; Muhammad, Danang Wahyu (Al-Risalah, 2021)
The institutions involved in fiduciary guarantee services are constantly and continuously developing due to the increasing and evolving needs of the surrounding community. This directly impacts the people defaulting on their fiduciary guarantees or unable to repay their debts. In this case, debt transfers are often observed, requiring a down payment or guarantee money for the first one or two months. Debtors also commonly struggle to make subsequent payments, as they prioritize new goods or other secondary needs. This leads to defaults on transactions initiated by the debtor, ultimately causing harm to the creditor institution in terms of transferring fiduciary guarantee objects. Therefore, this study aims to compare the regulation of fiduciary guarantee objects transfer from the perspective of Islamic law. In this case, a qualitative research approach was employed by conducting a normative juridical analysis. A comparison was also carried out between the doctrines of formal and Islamic law within the local community. The results obtained are expected to minimize instances of default by debtors and protect the interests of creditors when transferring the objects of fiduciary guarantees in the future.